The Emerald guide to Talcott Parsons - Scott, John (Bingley, U.K. : Emerald Publishing Limited, 2020)
This book is an introductory guide to the work of Talcott Parsons, designed specifically for students and those new to his work. It offers a comprehensive guide to reading and understanding the development of Parsons' sociological ideas, placing them in the context of his life and his position in American sociology. Scott delves into crucial resources on Parsons, including a bibliography of key works and a guide to further reading. By equipping readers to understand Parsons, the author arms them to engage with Parsons' work for themselves and to come to their own, informed judgments about his contemporary relevance.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Parsons, Talcott, -- 1902-1979.; Sociology -- United States -- History; Social Science -- Sociology -- General; Social theory